NON-STEADY-STATE FLOW OF REAL INCOMPRESSIBLE FLUID IN PIPE WITH POROUS WALLS - Babajanyan, G. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
Non-steady-state flow of real incompressible liquid in a cylindric pipe with porous lateral surfaces is investigated. Nonstationarity of the problem is conditioned by non-steady-state movement of the fluid which is expressed in differential equations of motion. The problem is solved by the operational calculus method by use of Laplace double integral transformations on spatial and time coordinates. Characteristics of the flow motion are determined as functions of spatial and time coordinates.
Keywords: real incompressible liquid; cylindric pipe; non-steady-state flow; operational calculus method